2011
DOI: 10.1007/8904_2011_63
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Phenotype of Fabry Disease in a Patient with Pseudoobstruction Syndrome

Abstract: Fabry disease is a rare, X-linked inborn error of glycosphingolipid metabolism caused by a deficiency of the lysosomal enzyme a-galactosidase A. Progressive deposition of GL-3 starts early in life, presumably as early as in fetal life. Chronic burning or provoked attacks of excruciating pain in hands and feet in Fabry disease are common in most children as well as GI-symptoms.We describe a case of pediatric Fabry disease with gastrointestinal dysmotility symptoms as primary and most severe complaints. Colonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 13 publications
1
11
1
1
Order By: Relevance
“…These were mostly mild to moderate in severity, although 4 (13%) patients experienced severe abdominal pain. One of these patients had been the subject of a separate, independent report, due to the unusually severe GI manifestations [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…These were mostly mild to moderate in severity, although 4 (13%) patients experienced severe abdominal pain. One of these patients had been the subject of a separate, independent report, due to the unusually severe GI manifestations [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although heterozygous females were previously considered carriers, almost half of females may experience gastrointestinal symptoms and some of those symptoms, such as constipation, are reported almost twice as often by female patients as by male patients . In some cases the gastrointestinal symptoms can dominate the clinical picture, presenting as a so‐called ‘gastrointestinal phenotype’ of Fabry disease . It is well known that gastrointestinal involvement can be the first and only manifestation of Fabry disease for years.…”
Section: Discussionmentioning
confidence: 99%
“…GI symptoms are some of the earliest and most commonly reported symptoms in Fabry disease, and include abdominal pain, bloating, diarrhoea, constipation, nausea, and vomiting [101,140,143,144]. One study found that GI symptoms occurred in approximately 60% of children and in 50% of adults, and had a serious negative effect on QoL [143].…”
Section: Gastrointestinal Dysfunctionmentioning
confidence: 99%